Difficulties preventing the success of productive families programs projects in Jordan – A case study of Irbid Governorate during the period (2012- 2013) – - Alshraiedah, Bushra Waleed (Journal of Humanities & Social Sciences, 2020)
The study aimed to identify the characteristics of families benefiting from the program of productive families, and to identify the difficulties that prevent the success of the project, and the study community may have been from (269) poor families who benefited from this program in Irbid Governorate, which was chosen in a way of comprehensive survey method for all beneficiaries. They are distributed among (9) directorates within the governorate of Irbid (the Casbah of Irbid, Bani Kinana, Ramtha, Northern Mazar, Bani Ubaid, Koura, Northern Aghwar, Wasitiya, and Taibah). The study used the questionnaire as a study tool to reach the goals. The results of the study showed that the majority of the members of the study population are married males who take care of families whose number ranges between 5- 9 individuals, and that the educational level of the majority of them falls within the secondary stage or less, and that among them is not a small percentage of non- believers in health and do not have housing, The study found a set of difficulties that hinder the success of the project that prevents its continuation, represented by the lack of capital or financing, inefficiency and lack of experience with a high degree.